The lives of weeds opportunism, resistance, folly - Cardina, John, 1953- (Comstock Publishing Associates, an imprint of Cornell University Press, 2021)
"The natural histories of eight ordinary plant species transformed into noxious weeds through mostly well-intended human efforts to get rid of them show how lives of people and weeds are entangled in ways that reflect human beliefs and attitudes toward the natural world"--